LEVEL KOGNITIF SOAL DALAM BUKU BAHASA INDONESIA KELAS X TERBITAN KEMENDIKBUDRISTEK BERDASARKAN TAKSONOMI ANDERSON DAN KRATHWOHL - Wulansari, Keken; Mulyati, Yeti (Universitas Islam Sumatera Utara, 2023)
Important to pay attention to the cognitive level contained in the questions in class X Indonesian textbooks published by the Ministry of Education and Research and Technology so that success in learning can be measured. This study uses a qualitative method with a content analysis approach. The purpose of this study is to describe the items contained in Indonesian language textbooks for class X published by the Ministry of Education and Culture. The theory used is cognitive level based on Anderson and Krathwohl's taxonomy. Cognitive levels based on Anderson and Krathwohl's taxonomy are divided into six classifications, namely remembering (C1), understanding (C2), applying (C3), applying (C4), evaluating (C5), and creating (C6). The results in this study were that the level of questions most commonly found in class X Indonesian textbooks was the applying level (C4) which was 27.43% and the least applying (C3) was 3.98%.